Determination and clinical assessment of brain death. A historical panorama - Puca, Antonio (Medicina e Morale, 1991)
The debate on deterrnining death, is still connected to the question of organ transplantation. History shows how, starting from Mollaret and Goulon's definition of "coma dèpassè" in 1959 and the Harvard Medical School Ad Hoc Committee's definition of "irreversible coma" in 1968, the concept of brain death has been introduced amongst not only the medical professional categories but also in almost all the national legislations, as sufficient and necessary for the transplantation of organs "ex cadavere". This shows the differentiation between the concept of "whole brain death", maintained by the President's Commission and by the most of the European countries as by well as other countries and cultures, and the concept of "brain stem death", codified in the United Kingdom, in Canada and in Australia.